International Environmental Agreements with Uncertainty, Learning and Risk Aversion - Michael Finus; Pedro Pintassilgo; Alistair Ulph (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper analyses the formation of international environmental agreements (IEAs) under uncertainty, focusing on the role of learning and risk aversion. It bridges two strands of literature: one focused on the role learning for the success of IEA formation when countries are risk neutral and another that explores the implications of uncertainty and risk aversion on IEA formation under no learning. Combining learning and risk aversion seems appropriate as the uncertainties surrounding many international environmental problems are still large, those uncertainties are often highly correlated as for instance in climate change and hence pooling risks may be limited, but those uncertainties are gradually reduced over time through learning. It is shown that the negative conclusion with respect to the role of learning derived for risk neutrality has to be qualified: below a threshold level of risk aversion learning can impact positively on the success of IEAs, above the threshold the opposite is true. Moreover, in a world without full learning (i.e. partial and no learning), risk aversion can lead to better outcomes, but only if risk aversion is sufficiently high.
Keywords: C72; D62; D80; Q54; 330; international environmental agreements; uncertainty; learning and risk aversion; game theory